(untitled) (Research, Society and Development, 2022)
To enable meaningful learning, it is necessary to use varied methodologies where the student can be active in their own learning. The field class is one of these teaching methodologies that allow greater autonomy for students. Thus, the objective of this research was to evaluate the learning situations of the Morphology and Anatomy of Spermatophytes course of the Biological Sciences undergraduate program (CCB), inserted in the Health Sciences Center (CCS) of the State University of Ceará (UECE). To this end, three questionnaires were prepared, with objective and discursive questions, which were applied to students during the year 2018. From the analysis of the three questionnaires applied, it was possible to conclude that the field class enriched and facilitated the learning of the students. This is because higher grades were achieved, and consequently a higher average grade, during the reapplication of the multiple-choice questionnaire, which took place after each field class. This improvement is probably related to the student’s well-being. During field classes, it was observed that students were more curious and excited than during theoretical classes.